2018
DOI: 10.1142/s0219877018500074
|View full text |Cite
|
Sign up to set email alerts
|

Additive Manufacturing in SMEs: Empirical Evidences from Italy

Abstract: Research on innovative technological methods in SMEs' production processes is progressively receiving attention. However, little is known about the emerging phenomenon of Additive Manufacturing (AM), which may represent a significant strategic lever for fostering a company's competitiveness and performance, especially for SMEs. Our aim is to investigate the effects of AM on SMEs' production process, in order to better understand the relative outcomes of such an innovative technique. We used latent content anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 72 publications
0
11
0
Order By: Relevance
“…Several scholars have demonstrated that the organizational ability to pursue two dissimilar things at the same time, i.e. manufacturing efficiency and flexibility (Raisch et al, 2009); differentiation and low-cost strategic positioning (Porter, 1980); and global integration and local responsiveness ( Junni et al, 2013) seems a determinant of organizations' survival and performance (Zollo et al, 2015(Zollo et al, , 2016Marzi, Zollo, Boccardi and Ciappei). Consequently, an ambidextrous organization is thus identifiable as an organization capable of simultaneously exploring its environment and exploiting emerging opportunities or, in other words, an organization capable of pursuing current processes while continuously adapting to the changing competitive environment ( Junni et al, 2013).…”
Section: Theoretical Background 21 Ambidextrous Organizations and Agilitymentioning
confidence: 99%
“…Several scholars have demonstrated that the organizational ability to pursue two dissimilar things at the same time, i.e. manufacturing efficiency and flexibility (Raisch et al, 2009); differentiation and low-cost strategic positioning (Porter, 1980); and global integration and local responsiveness ( Junni et al, 2013) seems a determinant of organizations' survival and performance (Zollo et al, 2015(Zollo et al, , 2016Marzi, Zollo, Boccardi and Ciappei). Consequently, an ambidextrous organization is thus identifiable as an organization capable of simultaneously exploring its environment and exploiting emerging opportunities or, in other words, an organization capable of pursuing current processes while continuously adapting to the changing competitive environment ( Junni et al, 2013).…”
Section: Theoretical Background 21 Ambidextrous Organizations and Agilitymentioning
confidence: 99%
“…As faster diffusion of innovations in larger firms is a well-known phenomenon (van de Vrande et al. , 2009) and has been observed for AM (Marzi et al. , 2018), our focus reflects the current activities in industrial AM well.…”
Section: Methodsmentioning
confidence: 99%
“…Today’s conventional manufacturing processes such as machining, molding, casting and forging, constrain a part’s shape and strength, increase the amount of material and weight and limit the product’s performance. AM has the potential to be the alternative, viable transformation technology for the SMMEs (Marzi et al , 2018). This technology has proven its effectiveness in the areas where it is required to manufacture complex objects by impacting the cost of production, especially to transform a small-scale production into a large-scale one.…”
Section: Literature Reviewmentioning
confidence: 99%